Determination of antagonistic activity of extracts of medicinal plants on oral bacteria - Borysenko, Y. V.; Baranovskyi, M. M. (Problems of Environmental Biotechnology, 2018)
Last decade’s apparent problem is concerned with the use of synthetic medicines. Natural products provide unlimited opportunities for new drug discoveries. Human host and its microbial flora constitute a complex ecosystem. Any shifts in such equilibrium could cause the development of infectious diseases. It is important to determine the features of antagonistic properties of herbs’ extracts in order to develop drugs for the treatment and prevention of infectious diseases as the one of the most urgent task of modern biotechnology.